Impact of Dapivirine and Placebo Vaginal Rings on the Microbiota of Adolescent, Lactating, and Postmenopausal Females. (4th December 2021) - Austin, Michele N; Meyn, Leslie A; Avolia, Hilary A; Petrina, Melinda A; Cosentino, Lisa A; Alphonse, Calins; Chen, Beatrice A; Bunge, Katherine; Noguchi, Lisa; Beigi, Richard; Squires, Kathleen; Hillier, Sharon L
Abstract: Background: A 25-mg dapivirine vaginal ring has been demonstrated to reduce risk of human immunodeficiency virus (HIV) acquisition in nonpregnant adult women. In this secondary analysis of studies conducted in US adolescent, lactating, and postmenopausal females, vaginal microbiota was assessed prior to and after ring use, and between dapivirine and placebo ring users. Methods: Vaginal fluid swabs were collected before and after product use for the evaluation of microbiota using Nugent criteria, quantitative culture, and quantitative polymerase chain reaction. Results: Vaginal ring use did not impact bacterial vaginosis prevalence among the 3 populations and was associated with minimal shifts in microbiota. Adolescents in both arms demonstrated an increased prevalence of Lactobacillus crispatus and a decrease in quantity of Megasphaera lornae . Postmenopausal active and placebo ring users demonstrated an increased prevalence of lactobacilli and non- albicans yeast, while dapivirine ring users demonstrated an increased prevalence of Candida albicans and increased quantity of group B Streptococcus and non- albicans yeasts. Prevotella species were increased in lactating women, whereas Prevotella timonensis increased in prevalence and concentration among adolescent and postmenopausal females and Prevotella bivia increased in prevalence among adolescent dapivirine ring users. Conclusions: Dapivirine vaginal ring use was associated with minimal changes in the vaginal microbiota that are likely not clinically significant. Abstract : The impact of the dapivirine vaginal ring, a product for prevention of HIV in women, on the vaginal microbiota of adolescent, lactating, and postmenopausal women was evaluated. There was a minimal impact of ring use on the vaginal microbiota.